Fatimid coins minted in Palestine during the reigns of the two caliphs Almsatʻly billāh and Al-āmir bʼḥkam Allāh 487-524 AH / 1094-1130 AD (Sirte University Journal of Humanities, 2024)
This research deals with the study of the monetary system in Palestine during the reigns of the two Fatimid caliphs, Al-Musta’li Billah and his son, Al-Amir bi-Ahkam Allah, in the period of time extending between 487-524 AH / 1094-1130 AD, which is the period that witnessed the decline of the dependence of the Fatimid monetary system in Palestine to one metal, which is gold. Until it stopped completely in the year 520 AH / 1126 AD.It was shown through the study that Palestine minted gold dinars and their parts during the reign of Al-Mustali Billah in one mint, which was the city of Akka, after the decline of Fatimid rule in some coastal Palestinian cities, while dinars were minted during the reign of Al-Amir Bi-Ahkam Allah in three mints, which were Ashkelon, Akka. And Ayla, The coins recorded the attempt of the Fatimids in alliance with the Turks to reclaim Acre and liberate it from the grip of the Crusaders for two years, 506 and 507 AH. they minted Fatimid dinars there before the Crusaders reoccupied it again.The research methodology is the statistical and documentary study method supported by historical and technical analysis. The research material was collected from well-known international catalogs, specialized books and research, and reliable Internet sites.
Keywords: Acre; Ashkelon; Dinar; Fatimiyah; Palestine